Improving the Performance of Technical and Tactical Actions in Sambo - PhD, docent Sh.Sh.Gaziev; Student S.Z.Nurullaev (Genius Journals, 2023)
This thesis presents an analysis of the study of the technical and tactical actions of sambo wrestlers, which represents the beginning of a reception in the stance and the transition of technical actions to the stalls. The conclusions on the development of the performed attacking actions in the stalls without stopping from the beginning of the reception from the rack are briefly stated. A survey had conducted among sambo wrestlers, which includes 20 questions. Based on the results of the survey, we determined the importance of technical actions in the wrest against stalls.
Keywords: wrestling; sambo; technique